Does Frankie Go to Hollywood? From American influence to articulatory phonetics: the singing pronunciation of 1980s pop artists - Coline Caillol; Emmanuel Ferragne (Anglophonia)
This article draws inspiration from Trudgill’s foundational paper on pop song pronunciation, where he found that certain British artists such as The Beatles tended to sing in what could be described as an American-influenced accent. Over the years, this explicit influence has become enregistered as a Pop Song English (PSE) variety in its own right. The aim of this paper is to study this phenomenon with 1980s pop productions since that era marked a turning point in the history of how pop music was produced and commercialized. A quantitative study of word internal intervocalic /t/ pronunciation as a marker of an American accent (where a flapped alveolar realization is considered typically American as opposed to a more characteristically British alveolar stop) was carried out on a database of 350 randomly sampled songs from top 10 albums for each year of the decade. Despite some variation, most singers realize a majority of their /t/ as a flap in sung productions, something that is not seen in their spoken productions. Traditional sociocultural arguments pertaining to the influence of the American music industry and American-born music genres are presented, supported by some of the artists’ own viewpoints collected interviews freely available online. The outlines of an additional, articulatory account for this accent shift are delineated, looking into the specificity of the singing voice and its inherent pronunciation constraints. The idea that Pop Song English has become a pronunciation standard also because of more phonetic and functional reasons is posited, though experimental evidence remains to be provided.